2016
DOI: 10.1002/mabi.201600016
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo and In Vitro Studies on the Cytotoxicity and Immunomodulative Properties of Poly(2‐isopropenyl‐2‐oxazoline) as a New Type of Biomedical Polymer

Abstract: Poly(2-alkenyl-2-oxazoline)s are promising functional polymers for a variety of biomedical applications, such as drug delivery systems, peptide conjugates, or gene delivery. In this study, poly(2-isopropenyl-2-oxazoline) (PIPOx) is prepared through free-radical polymerization initiated with azobisisobutyronitrile. Reactive 2-oxazoline units in the side chain support an addition reaction with different compounds containing a carboxylic group, which facilitates the preparation of polymers labeled with two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 56 publications
4
56
0
Order By: Relevance
“…One of the potential alternatives to polyethers such as PEG and Pluronics, in particular for medical applications, are poly(2‐alkyl‐2‐oxazoline)s (POx) . Poly(2‐ethyl‐2‐oxazoline) and poly(2‐methyl‐2‐oxazoline) were found nontoxic toward fibroblast cells up to concentrations of 10–20 g L −1 . Amphiphilic diblock and triblock copoly(2‐oxazolines) were shown to be nontoxic toward human breast cancer cells and canine kidney cells up to the concentrations 10 g L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the potential alternatives to polyethers such as PEG and Pluronics, in particular for medical applications, are poly(2‐alkyl‐2‐oxazoline)s (POx) . Poly(2‐ethyl‐2‐oxazoline) and poly(2‐methyl‐2‐oxazoline) were found nontoxic toward fibroblast cells up to concentrations of 10–20 g L −1 . Amphiphilic diblock and triblock copoly(2‐oxazolines) were shown to be nontoxic toward human breast cancer cells and canine kidney cells up to the concentrations 10 g L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…10 g/L and 20 g/L, respectively. Compared to 2-oxazolines (MeOx, EtOx) the cytotoxicity of 2-oxazines is about one order of magnitude lower [23] . This may reflect the lower reactivity of the 2-oxazines compared to the 2-oxazolines.…”
Section: Cytotoxicity Of Monomersmentioning
confidence: 97%
“…An important argument that moves PiPOx polymer forward to a variety of biological applications, is the recent report by Kronek's group concerning PiPOx's biocompatibility. 62 Consequently, we investigated the cytotoxic nature of PiPOx using MTT cytotoxicity assay to determine if there is any difference between the polymer obtained by radical (Kronek's study) and anionic polymerization (present study). The cytotoxicity studies revealed that the non-toxic concentration for a cell viability higher than 80% is 13.5 mg/mL after 24 h of incubation (Fig.…”
Section: Direct Cytotoxicity Assaymentioning
confidence: 99%
“…The results obtained are similar with those reported by Kronek. 62 Furthermore, we performed a cytotoxicity assay of the hydrogels to assess their use as potential biomaterials. For this test we used the hydrogel cross-linked with azelaic acid.…”
Section: Direct Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation